Edukasi Pengelolaan Sampah Melalui Penerapan Eco-Enzyme di Lingkungan Ponpes Darunnasikah NW Pringgasela - Nishfiya Ramdoniati; Andri Afriani; Helmi Najamudin (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2026)
Islamic boarding schools are educational institutions that generate organic waste daily, primarily from kitchen and canteen activities as well as leftover food from students. Improperly managed organic waste leads to various negative impacts, such as environmental pollution, unpleasant odors, the proliferation of pathogenic microorganisms, the emission of methane gas (which contributes to global warming), and adverse effects on human health. Eco-enzyme is a liquid produced by fermenting organic waste—such as fruit peels and vegetable scraps—with a mixture of sugar and water over a period of approximately three months. The methodology employed in this community service activity comprised four stages: 1) planning, 2) implementation, 3) observation, and 4) evaluation. The activity involved 15 participants, consisting of 10 students and 5 supervising teachers. The results indicate an improvement in the participants' knowledge and skills regarding organic waste management through the use of eco-enzymes, evidenced by the increase in average pre-test and post-test scores. Observations also showed that the participants actively engaged throughout the activity.